Isolation and Genome Analysis of an Amoeba-Associated Bacterium Dyella terrae Strain Ely Copper Mine From Acid Rock Drainage in Vermont, United States - Giddings, Lesley-Ann; Kunstman, Kevin; Moumen, Bouziane; Asiama, Laurent; Green, Stefan; Delafont, Vincent; Brockley, Matthew; Samba-Louaka, Ascel (Frontiers in Microbiology, 2022)
Protozoa play important roles in microbial communities, regulating populations via predation and contributing to nutrient cycling. While amoebae have been identified in acid rock drainage (ARD) systems, our understanding of their symbioses in these extreme environments is limited. Here, we report the first isolation of the amoeba Stemonitis from an ARD environment as well as the genome sequence and annotation of an associated bacterium, Dyella terrae strain Ely Copper Mine, from Ely Brook at the Ely Copper Mine Superfund site in Vershire, Vermont, United States. Fluorescent in situ hybridization analysis showed this bacterium colonizing cells of Stemonitis sp. in addition to being outside of amoebal cells. This amoeba-resistant bacterium is Gram-negative with a genome size of 5.36 Mbp and GC content of 62.5%. The genome of the D. terrae strain Ely Copper Mine encodes de novo biosynthetic pathways for amino acids, carbohydrates, nucleic acids, and lipids. Genes involved in nitrate (1) and sulfate (7) reduction, metal (229) and antibiotic resistance (37), and secondary metabolite production (6) were identified. Notably, 26 hydrolases were identified by RAST as well as other biomass degradation genes, suggesting roles in carbon and energy cycling within the microbial community. The genome also contains type IV secretion system genes involved in amoebae resistance, revealing how this bacterium likely survives predation from Stemonitis sp. This genome analysis and the association of D. terrae strain Ely Copper Mine with Stemonitis sp. provide insight into the functional roles of amoebae and bacteria within ARD environments.